Russia’s “Pivot” to the East: Short-lived with China? - Cheang, Chris (2017)
Since the Ukrainian and Crimean crises, much has been written about Russia’s “pivot” to the East, chiefly China. The gravity of the current tensions between Russia and the West has, however, been exaggerated. Russia’s culture, history, and geography have inextricably been tied to the Western/European world.